1999
DOI: 10.4141/a98-108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of housing conditions on responses of pigs to preslaughter treatment and consequences for meat quality

Abstract: . 1999. Influence of housing conditions on responses of pigs to preslaughter treatment and consequences for meat quality. Can. J. Anim. Sci. 79: 285-291. The effects of housing conditions on behavioural and cortisol responses during preslaughter treatment, as well as the consequences for meat quality, were studied in 48 slaughter pigs. Pigs were either raised in intensive housing conditions ("standard" treatment: standard farrowing crates (4.2 m 2 ) followed by standard rearing pens (0.5 m 2 /pig) and fattenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
37
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 23 publications
12
37
1
3
Order By: Relevance
“…Thus, the A system did not modify the behaviour and physiological responses of either LW or B pigs to the preslaughtering procedure, which is in accordance with previous results on A v. C system comparisons (Lebret et al, 2006 and. Other studies also showed no effect of enriched environment (increased space allowance, straw bedding) on physiological stress indicators assessed at the end of the lairage period, although the housing conditions influenced animal activity during transport (Geverink et al, 1999;Klont et al, 2001). Conversely, Foury et al (2011) Lebret, Ecolan, Bonhomme, Méteau and Prunier skin lesions and lower plasma CK at slaughter in pigs housed on sawdust bedding with outdoor access compared with conventional housing; however, in their study, pigs were slaughtered in an industrial slaughterhouse, generating more stressful conditions as demonstrated by the much higher average levels of skin lesions and plasma CK levels compared with the present study.…”
Section: Resultssupporting
confidence: 90%
“…Thus, the A system did not modify the behaviour and physiological responses of either LW or B pigs to the preslaughtering procedure, which is in accordance with previous results on A v. C system comparisons (Lebret et al, 2006 and. Other studies also showed no effect of enriched environment (increased space allowance, straw bedding) on physiological stress indicators assessed at the end of the lairage period, although the housing conditions influenced animal activity during transport (Geverink et al, 1999;Klont et al, 2001). Conversely, Foury et al (2011) Lebret, Ecolan, Bonhomme, Méteau and Prunier skin lesions and lower plasma CK at slaughter in pigs housed on sawdust bedding with outdoor access compared with conventional housing; however, in their study, pigs were slaughtered in an industrial slaughterhouse, generating more stressful conditions as demonstrated by the much higher average levels of skin lesions and plasma CK levels compared with the present study.…”
Section: Resultssupporting
confidence: 90%
“…Similarly, other studies found that pigs reared outdoors show less aggressive interactions after mixing at loading, during transport and lairage than conventionally reared pigs, even with the same level of mixing (Barton Gade, 2008a;Terlouw et al, 2009). In accordance with previous studies investigating either urinary (Lebret et al, 2006 and2011) or plasma or salivary cortisol (De Jong et al, 1998 andGeverink et al, 1999;Klont et al, 2001;Lebret et al, 2006;Barton Gade, 2008a and2008b), urinary cortisol levels were not affected by the rearing system. Whatever the rearing system, pigs from station 3 exhibited the lowest levels of physical activity and/or stress indicators (plasma CK, cortisol and catecholamines) at slaughter.…”
Section: Discussionsupporting
confidence: 75%
“…Outdoor or environmentally enriched systems are better perceived than conventional (CON) intensive systems by modern consumers, as CON housing provides a barren environment to animals and prevents them from expressing their natural behaviors (Dransfield et al, 2005;Edwards, 2005). Several studies showed that, in comparison to indoor-reared animals, pigs reared in ALT systems are less aggressive and less active during transport and lairage periods (Geverink et al, 1999;De Jong et al, 2000;Barton Gade, 2008a and2008b;Terlouw et al, 2009). Many studies also show that rearing conditions may affect meat quality.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that rearing at high density or under barren conditions may disturb the normal development of social behaviour or increase fearfulness, resulting in increased aggression (Schouten, 1986;de Jonge et al, 1996;Olsson et al, 1999;O'Connell et al, 2004). Pigs reared under standard intensive conditions were easier to load, but showed a stronger increase in salivary cortisol during transport and lairage than pigs reared in larger pens or in an enriched environment and their meat had more drip loss (Geverink et al, 1999;De Jong et al, 2000;Klont et al, 2001;Chaloupkova et al, 2007), although opposite results have also been reported (Lambooij et al, 2004).…”
Section: Pigsmentioning
confidence: 97%